World NTD Day 2022 and a new Kigali Declaration to galvanise commitment to end neglected tropical diseases - Thoko Elphick-Pooley; Dirk Engels; Uniting to Combat NTDs (BMC, 2022)
Abstract The World Health Organization's first roadmap and the London Declaration on neglected tropical diseases (NTDs) have allowed an unprecedented expansion of interventions to control and eliminate this group of infectious diseases that primarily affects vulnerable or marginalised communities. The 2021-2030 NTD roadmap sustains a further acceleration of interventions but also introduces a broader and more ambitious agenda, calling to be accompanied by a new political declaration. Sponsored by the Government of Rwanda, the Kigali Declaration on neglected tropical diseases will be launched in 2022 to renew and reinvigorate commitments to end NTDs, also in the wake of the current setback caused by the COVID-19 pandemic. Starting on World NTD Day 2022, a global campaign "100% Committed" will call on a broad range of stakeholders to sign the declaration and make bold financial and political commitments towards achieving the 2030 roadmap and Sustainable Development Goals' targets for NTDs.